PENDAMPINGAN UMKM DESA KEBUYUTAN KECAMATAN WANASALAM MELALUI STRATEGI PEMASARAN ONLINE UNTUK KELOMPOK USAHA BERSAMA “KARYA MANDIRI” - Basuki Rakhim Setya Permana; Fajri Fatullah; Kayla Maharani; Mochammad Darif; Gelard Untitha Pratama (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The aim of this study is to explore the marketing approaches employed by MSME players, particularly in Serang City. A notable method they use is E-commerce, a digital means of purchasing and selling items. Over time, E-commerce has expanded and is gradually taking over traditional storefronts. This study utilizes a descriptive qualitative data analysis approach, focusing on portraying the situation as it stands without alterations or manipulation to the studied variables. The only intervention in the study is the research process itself, which involves observations, interviews, and documentation. The findings reveal that MSMEs in Serang City predominantly leverage E-commerce as a marketing tool, enhancing their product sales and proficiency